Simulating Intestinal Growth Conditions Enhances Toxin Production of Enteropathogenic Bacillus cereus - Jeßberger, Nadja; Rademacher, Corinna; Krey, Viktoria M.; Dietrich, Richard; Mohr, Ann-Katrin; Böhm, Maria-Elisabeth; Scherer, Siegfried; Ehling-Schulz, Monika; Märtlbauer, Erwin (Frontiers in Microbiology, 2017)
Bacillus cereus is a ubiquitous bacterial pathogen increasingly reported to be the causative agent of foodborne infections and intoxications. Since the enterotoxins linked to the diarrheal form of food poising are foremost produced in the human intestine, the toxic potential of enteropathogenic B. cereus strains is difficult to predict from studies carried out under routine cultivation procedures. In this study, toxigenic properties of a panel of strains (n=19) of diverse origin were compared using cell culture medium pre-incubated with CaCo-2 cells to mimic intestinal growth conditions. Shortly after contact of the bacteria with the simulated host environment, enterotoxin gene expression was activated and total protein secretion of all strains was accelerated. Although the signal stimulating enterotoxin production still needs to be elucidated, it could be shown that it originated from the CaCo-2 cells. Overall, our study demonstrates that the currently used methods in B. cereus diagnostics, based on standard culture medium, are not allowing a conclusive prediction of the potential health risk related to a certain strain. Thus, these methods should be complemented by cultivation procedures that are simulating intestinal host conditions.